2011
DOI: 10.1007/s00213-011-2445-7
|View full text |Cite
|
Sign up to set email alerts
|

The missing variable: ultrasonic vocalizations reveal hidden sensitization and tolerance-like effects during long-term cocaine administration

Abstract: Rationale Subtypes of 50-kHz ultrasonic vocalizations (USVs) in rats are thought to reflect positive affect and occur with cocaine or amphetamine delivery. In contexts predicting forthcoming cocaine, pre-drug anticipatory USVs are initially minimal during daily sessions but gradually escalate over several weeks, presumably as the animal learns to expect and look forward to impending drug access. To gain more insight into motivational aspects of cocaine intake in animal models of drug dependence studies, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
3
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 66 publications
5
46
3
1
Order By: Relevance
“…In line with this idea, additional studies have shown that individuals exhibiting USV sensitization to psychostimulant drugs will also display a conditioned escalation in USVs in response to the drug-associated context alone (Ahrens et al 2009; Meyer et al 2012b; Simola and Morelli 2015). Although our study did not specifically test context-induced USVs, it can be noted that some sign-trackers immediately began producing USVs upon entering the chamber on all days following the first cocaine treatment, even though peak levels of cocaine in the brain are not achieved until 10 minutes after the injection (Javaid and Davis 1993; Maier et al 2012). These USVs could be a result of the conditioned effects of the context itself, possibly in anticipation of cocaine's effects (Ma et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this idea, additional studies have shown that individuals exhibiting USV sensitization to psychostimulant drugs will also display a conditioned escalation in USVs in response to the drug-associated context alone (Ahrens et al 2009; Meyer et al 2012b; Simola and Morelli 2015). Although our study did not specifically test context-induced USVs, it can be noted that some sign-trackers immediately began producing USVs upon entering the chamber on all days following the first cocaine treatment, even though peak levels of cocaine in the brain are not achieved until 10 minutes after the injection (Javaid and Davis 1993; Maier et al 2012). These USVs could be a result of the conditioned effects of the context itself, possibly in anticipation of cocaine's effects (Ma et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, drugs including cocaine have other unconditioned effects, including the ability to elicit 50 kHz ultrasonic vocalizations (USVs; Browning et al 2011; Ma et al 2010; Maier et al 2012; Meyer et al 2012b). These USVs have been proposed to have a communicative purpose, and also to serve as an expression of motivational and affective states in rodents (Knutson et al 2002; Portfors and Perkel 2014; Radziwon and Dent 2014; Brudzynski 2013; Wohr and Schwarting 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Rodents emit USVs in the 50–55 kHz and 22–28 kHz ranges, which are reliably associated with positive and negative emotional states, respectively [15–17]. USVs have received increased attention in drug abuse studies because administration of cocaine [18], amphetamine [19] and drug-associated cues [20, 21] increase 50–55 kHz frequency-modulated (FM) USV emissions. In addition, escalated levels of alcohol consumed by alcohol-dependent rats are significantly correlated with alcohol anticipatory 50–55 kHz FM USVs [22] and alcohol-dependent rats in a state of withdrawal are more easily provoked to emit negative affect-associated 22–28 kHz USVs by mild aversive stimuli [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic vocalizations have recently come to attention as potential measures of the emotional and motivational states of rats, including reward (Panksepp & Burgdorf, 2000; Browning et al, 2011; Maier et al, 2012; Mu et al, 2009). Specifically, 50 kHz vocalizations are typically emitted in reinforcer-associated contexts (Brunelli et al, 2006; Knutson et al, 1998; Panksepp & Burgdorf, 2000; Sales, 1972; Schwarting et al, 2007; White et al, 1990) while 22 kHz vocalizations are generally associated with aversive situations (Francis, 1977; Jelen et al, 2003; Tonoue et al, 1986; Wohr et al, 2005; Mead et al, 2008; Sun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%